DESIGNING A TRIMARAN FISHING BOAT TO IMPROVE WORK SAFETY FOR TRADITIONAL FISHERMAN IN INDONESIA - I Putu Arta Wibawa (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
As the second largest nation in capture fisheries in the world after China, Indonesia has a very large fleet of fishing boat. The main problems encountered on fishing vessels in Indonesia are the limited technology on board, and boat safety issues. One type of fishing boat that is common in Indonesia is a boat with “Cadik” or outrigger. The characteristics of an outrigger boat are the presence of a main hull with a length of between 7 meters - 12 meters, with a main hull width ranging from 0.9 meters - 1.2 meters. The shape of the main hull of the boat which tends to be long with a small width has problems in terms of boat stability, namely the boat is easy to roll, especially when fishermen are on one side of the boat to lower the net. To overcome this issue, fishermen generally install outriggers made of bamboo on both sides of the boat to increase the balance or stability of the boat. Based on this problem, a fishing boat was designed that applies the trimaran hull concept, which is the boat with three hulls. The function of the side-hull in addition to increasing the stability of the boat also as a compartment to store fishing gear and other fishing equipment. Meanwhile, the area between the main hull and the side-hull will function as a connecting deck, thus expanding the fishermen's working area and increasing the fishermen's work safety.